The eco-hedonic social segment of the Island of Santay Ecuador (Wetland 1041 Ramsar) and its willingness to pay (WTP) for its conservation - Quelal Mora, Judith Genoveva (2020)
The island of Santay, located in front of the city of Guayaquil, Ecuador, is a RAMSAR wetland of international relevance, in which the number of visitors has decreased due to its lack of maintenance. The objectives of this work are to find the willingness to pay (WTP) by visitors to this wetland and to evaluate the possibility of entertaining activities for ecohedonic families. For this, it is necessary to analyze the profile of the current visitor who arrives at the island of Santay and identify the variables that condition the WTP of the visitor with a predilection for these tourism destinations, but with better conservation. The research method has a positivist approach (quantitative), descriptive and bibliographic method. Data collection used the document analysis technique and checklists. The profile of the current visitor and the variables that determine the WTP are analyzed. The echohedonic segment is the most representative. However, 49% are not willing to pay for the little varied offer and its price. Likewise, the case studies of segmentation and motivations in ecotourism are analyzed by reviewing the scientific literature. The results are the basis for tourism actors considering joining the eco-hedonic-social segment with travel packages.